It's all about time: the influence of behaviour and timelines on suspect disclosure during investigative interviews - Bergeron, Andréanne (Policing and society, 2023)
Research on confession has usually focused on showing that it is significantly associated with individual, crime-related, and situational/contextual variables and is both a static event and a dichotomous indicator of interview success. Recent work, however, suggests that investigative interviews are a dynamic process in which interrogation strategies change over time. Using a Game Theory perspective, this study looks at the impact of behaviours of both players (interviewer and suspect) on the production of investigation-relevant information (IRI). The sub-objective is to demonstrate the usefulness of applying Game Theory to the study of investigative interviews by considering time and interaction between players as an integrative part of the analysis. Videotaped interviews related to online child sexual exploitation (n = 130) were analysed and the different behaviours of suspects and interviewers were analysed to determine if they involved (1) rapport building/active denial, (2) collaboration, (3) confrontation, (4) emotion/response, and (5) elicitation of information related to the case. Results showed that information relevant to the investigation is often provided shortly after a suspect has offered additional information or given responses that meet emotional needs (e.g. justifications). The interviewer's use of available evidence increases the likelihood that additional information will be provided, while the ability to build a rapport with the suspect is effective in the longer term, even if a positive effect is not immediately observed. Using a dynamic process approach in analysing investigative interviews provides a starting point for the creation of practical guidelines to help practitioners increase suspect collaboration during investigative interviews.